2017
DOI: 10.1590/1678-4162-8241
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e características de carcaça de três genótipos comerciais de frangos de corte alimentados com diferentes dietas

Abstract: RESUMO Este estudo teve como objetivo avaliar o desempenho e as características de carcaça de frangos de corte de três genótipos comerciais do nascimento aos 35 dias de idade. Utilizou-se um total de 2.970 pintos de três genótipos de aves comerciais (Cobb 500, Hubbard Flex e Ross 308). Os programas nutricionais foram dieta basal, dieta com 10% mais e 10% menos de aminoácidos do que a dieta basal. As aves foram distribuídas em delineamento inteiramente ao acaso, em esquema fatorial 3x3x2 (genótipo x dieta x sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
2
0
3
Order By: Relevance
“…Consequently, the use of DBR provided better WG, with similar FC, among all treatments studied (Table 2). The values found for FC are in agreement with those found by Silva (2013), who, in a study evaluating the productive potential of the Cobb lineage, observed 1,710 kg of feed per kg of chicken, for birds at 42 days of age. This result indicates that the inclusion of DBR, which despite having a high fiber content (NDF and ADF), did not represent a limiting role for the development of the birds, having little interference with the nutritional value of the diet.…”
Section: Resultssupporting
confidence: 90%
“…Consequently, the use of DBR provided better WG, with similar FC, among all treatments studied (Table 2). The values found for FC are in agreement with those found by Silva (2013), who, in a study evaluating the productive potential of the Cobb lineage, observed 1,710 kg of feed per kg of chicken, for birds at 42 days of age. This result indicates that the inclusion of DBR, which despite having a high fiber content (NDF and ADF), did not represent a limiting role for the development of the birds, having little interference with the nutritional value of the diet.…”
Section: Resultssupporting
confidence: 90%
“…Thus, because a greater villus height was found in the treatment with Enzymmix F without an increase in crypt depth (Table 7), it is understood that the product has the potential to improve intestinal quality. However, Silva et al (2011) submitted that the villus/crypt ratio is the best indicator of the digestive capacity of the small intestine, and this parameter did not differ across the treatments tested in the present study.…”
Section: Factormentioning
confidence: 41%
“…The use of the same ingredient base (corn and soybean) for the formulation of the diet as well as the same line of the birds likely contributed to this result. Differences in yields of carcass and cuts are more common when different raw materials (Geron et al, 2015;Frank et al, 2016), lines (Api et al, 2017;Silva et al, 2017) and diet physical forms (Oliveira et al, 2011) are used.…”
Section: Factormentioning
confidence: 99%
“…Não houve efeito significativo (P>0,05) entre as linhagens para o índice de viabilidade. Silva et al (2017) compararam a viabilidade criatória de linhagens comerciais e notaram maiores índices nos machos, além de apresentaram melhores desempenhos e características de carcaças do que as fêmeas.…”
Section: Resultsunclassified